Chế tạo và nghiên cứu tính chất vật liệu polyme nanocompozit từ cao su nitril và clay hữu cơ - Vũ, Phạm Gia; Hằng, Tô Thị Xuân; Phong, Võ Thành; Quang, Nguyễn (Vietnam Journal of Chemistry, 2012)
Rubber Clay-Nanocomposite based on nitril rubber and organic clay Nanofil 5 have been prepared. The mechanical properties of nanocomposite were evaluated by Zwick Materials Testing. The nanocomposite structure was analysed by Infrared Spectroscopy (IR), X-ray Diffraction (XRD) and Transmission Electronic Microscopy (TEM). The measured results showed that silicate layers was partly exfoliated, partly intercalated in the nitril rubber matrix. The presence of organic clay Nanofil 5 improved significantly mechanical properties of nitril rubber.